2021
DOI: 10.1111/acer.14537
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Cognition Deficits Recover with Abstinence in Alcohol‐Dependent Patients?

Abstract: Background Despite growing evidence of the presence and clinical relevance of deficits in social cognition in individuals with alcohol use disorder (AUD), less is known about the potential of “natural” recovery with abstinence in this neurocognitive domain. This study investigated the abstinence‐based recovery of neurocognitive social abilities in alcohol‐dependent patients (ADP) using a prospective longitudinal design with follow‐up assessment under controlled conditions of abstinence during alcohol dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“… Notes : Numbers refers to the study that did, or did not, found an association or effect (<.05) of the specific factor on neurocognitive recovery: 1 49 , 2 39 , 3 15 , 4 43 5 45 , 6 37 , 7 47 , 8 46 , 9 34 , 10 38 , 11 32 , 12 52 , 13 40 , 14 53 , 15 17 , 16 94 , 17 44 , 18 96 , (no factors), 19 48 , 20 28 , 21 31 , 22 35 , 23 51 , 24 95 , (no factors), 25 12 , 26 33 , 27 97 , 28 29 , 29 42 , 30 36 , 31 41 . Indication of level of evidence according to Oxford Classification for Evidence Based Medicine (OCEBM), varying from 1 (very strong) to 5 (very weak): a Level 2, b Level 3, c Level 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Notes : Numbers refers to the study that did, or did not, found an association or effect (<.05) of the specific factor on neurocognitive recovery: 1 49 , 2 39 , 3 15 , 4 43 5 45 , 6 37 , 7 47 , 8 46 , 9 34 , 10 38 , 11 32 , 12 52 , 13 40 , 14 53 , 15 17 , 16 94 , 17 44 , 18 96 , (no factors), 19 48 , 20 28 , 21 31 , 22 35 , 23 51 , 24 95 , (no factors), 25 12 , 26 33 , 27 97 , 28 29 , 29 42 , 30 36 , 31 41 . Indication of level of evidence according to Oxford Classification for Evidence Based Medicine (OCEBM), varying from 1 (very strong) to 5 (very weak): a Level 2, b Level 3, c Level 4.…”
Section: Resultsmentioning
confidence: 99%
“… 41 The abstinence duration periods ranged from 1 day 39 up to 48 months, 15 with most studies using abstinence periods within one year (8/11 studies). 18 , 28 , 34 , 36 , 38 , 40 , 41 Other studies have investigated neurocognitive recovery during abstinence periods up to 48 months. 15 , 37 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption is indeed sometimes used as a coping strategy to regulate emotional states and altered interpersonal relationships 37,38 . In addition, a recent study showed that social cognition deficits, including emotion recognition and affective responsiveness, did not spontaneously recover during the first months of abstinence 39 . Taken together, these findings highlight the relevance of developing therapeutic interventions to manage emotional deficits and ultimately reduce the risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrates associations between substance or alcohol use disorder and deficits in facial emotion recognition (Castellano et al 2015 ). Furthermore, these deficits may persist over time, despite abstinence (Rupp et al 2021 ). While facial emotion recognition accuracy has been evaluated among individuals with psychoactive substance dependence, this has not yet been examined within AAS dependence.…”
Section: Introductionmentioning
confidence: 99%